CONTENT VALIDITY AND RELIABILITY OF BUSS AND PERRY AGRESSIVE QUESTIOANNAIRE (BPAQ) INVENTORY - Ibrahim Abd Ghani; Norsayyadatina Che Rozubi, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study was conducted to measure the content validity and reliability of, Buss and Perry Aggressive Questionnaire (BPAQ). BPAQ questionnaire was translated into Bahasa Melayu in the past and has validity. For the validity of the content three experts in the field of counseling were appointed to assess the validity of the content to be used for the primary school sample. The findings show that experts have made suggestions for improvement in terms of content. 60 primary school students were sampled to measure the reliability of BPAQ instruments. The findings also show that the reliability coefficient obtained is .93 Based on the results of the study, the BPAQ measuring instrument has the potential to be used in measuring students' aggressive behavior.